ANALISIS MAKROEKONOMI TERHADAP PERGERAKAN INDEKS HARGA SAHAM GABUNGAN (IHSG) DI INDONESIA - Yuninda Anggraini Putri; Masruri Muchtar; Pardomuan Robinson Sihombing (LPPM Universitas Bina Bangsa, 2023)
Investors will always consider the movement of JCI in determining their investment decisions. This research examines the movement of inflation, the rupiah exchange rate, world gold prices, the DJIA stock index, and the FED rate against JCI movements. The test was conducted using the ECM (Error Corection Model) model where the results of this study can be taken into consideration by investors when investing in shares in the IDX capital market. Measurement of the relationship between the influence of macroeconomic factors on JCI movements starts from 2017 to 2021. The results found that in the long run inflation variables, the rupiah exchange rate, world gold price, DJIA stock index, and The FED rate simultaneously have a significant influence on JCI. Then in the short term inflation variables, the rupiah exchange rate, world gold prices, DJIA stock index, and The FED rate also have a simultaneous influence on the dependent variable of JCI. So by looking at the results of the influence of the five variables above on JCI, it can be used as a consideration for investors investing in shares on the IDX